2002
DOI: 10.1161/01.cir.0000021924.02006.ba
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Indirectly Upregulates Superoxide Dismutase Expression in Endothelial Cells via Vascular Smooth Muscle Cell–Dependent Pathways

Abstract: Background-Calcium antagonists normalize endothelial dysfunction in many cardiovascular diseases. There is no known receptor, however, for calcium antagonists in endothelial cells (ECs). We hypothesized that vascular smooth muscle cells (VSMCs) are involved in the mechanism underlying the normalization of endothelial dysfunction by calcium antagonists. Methods and Results-Coculture studies with ECs and VSMCs were performed to determine whether VSMCs mediate modulation of endothelial superoxide dismutase (SOD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 29 publications
4
41
1
1
Order By: Relevance
“…Secondly, our study demonstrated that NIF treatment significantly reduced the levels of hs-CRP and vWF compared with AML, and it suggested that NIF treatment may improve the vascular endothelial function. These findings are supported by reports that NIF has stronger anti-inflammatory activity 39 and stronger anti-atherosclerotic effects including an antioxidant action 40,41 than other CCBs. Recently, the ENCORE study from Europe 42 demonstrated that long-acting nifedipine GITS improves acetylcholine sensitivity in patients with coronary artery disease, suggesting that NIF treatment could also improve vascular endothelial function.…”
Section: Discussionsupporting
confidence: 82%
“…Secondly, our study demonstrated that NIF treatment significantly reduced the levels of hs-CRP and vWF compared with AML, and it suggested that NIF treatment may improve the vascular endothelial function. These findings are supported by reports that NIF has stronger anti-inflammatory activity 39 and stronger anti-atherosclerotic effects including an antioxidant action 40,41 than other CCBs. Recently, the ENCORE study from Europe 42 demonstrated that long-acting nifedipine GITS improves acetylcholine sensitivity in patients with coronary artery disease, suggesting that NIF treatment could also improve vascular endothelial function.…”
Section: Discussionsupporting
confidence: 82%
“…This result is also supported by our previous finding that nifedipine indirectly enhances NO production by endothelial cells by stimulating vascular endothelial growth factor release from the VSMCs. 23 Our present findings have the important implication that regeneration of endothelial cells and upregulation of endothelial NO synthase expression via Akt signaling activated by vascular endothelial growth factor and other growth factors may not be suppressed by calcium antagonists. 24,25 The number of functional L-type calcium channels significantly decreased in dedifferentiated VSMCs and increased on differentiation.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, our findings on plasma nitrate and nitrite concentrations and on superoxide anion generation are consistent with the interpretation that the availability of NO is inversely correlated with the magnitude of superoxide anion generation. VEGF has been reported to upregulate the expression of superoxide dismutase, a major superoxide scavenger, in endothelial cells [7]. Moreover, reductions in superoxide dismutase have been reported to inhibit endothelium-dependant relaxation through the inactivation of NO [4].…”
Section: Discussionmentioning
confidence: 99%
“…Treatments that preserve vascular function would therefore be of obvious therapeutic benefit. Vascular endothelial growth factor (VEGF) is a potential candidate as it has been reported to upregulate superoxide dismutase in isolated endothelial cells [7]. In view of the altered acetylcholine-evoked vascular responses typically seen in the diabetic state [3,8], we sought to determine whether chronic treatment with VEGF early in the disease can preserve 'normal' acetylcholine-evoked responses in these rats, despite their uncontrolled diabetes.…”
Section: Introductionmentioning
confidence: 99%